Composing for Wind Ensemble in the 21st Century. - Cunningham, Corey (My University, 2009)
During the last several decades, the wind ensemble has become a significant force supporting the commissioning and performance of newly composed music. Our research examines significant works by composers of wind ensemble music in the last 30 years, and strives to establish a set of criteria for works that successful in terms of their innovative potential and artistic longevity.
Color poster with text and images.
Keywords: Wind ensembles--Analysis, appreciation; Wind ensembles--History and criticism; Posters